Social Stereotypes of Youth in Perception of Image of Worker of National Police - Oleinyk, Narmina; Babatina, Svitlana; Korkos, Yaroslav (Psychological Prospects Journal, 2018)
The article is dedicated to investigation of social stereotypes in perception of image of police worker and their interrelation with education and gender affiliation of examinees. The problem of perception of lawmen is an important part of the reform of law-enforcement authorities because the adequate perception of policemen is connected with high level of confidence in them, prestigiousness, popularity of their profession etc. The purpose of the article is determination of structural peculiarities of perception of policeman image in daily living. The inquirer «Stereotypes about workers of police» was devised and used as psychognostic tooling for detection of social stereotypes, «The Bem Sex-Role Inventory» was used for establishing gender affiliation of examinees. Among the methods of statistical data analysis used in work are qualitative and quantitative analysis of results based on the procedure of factor analysis (STATISTICA 10.0), Fisher’s angular transformation, Pearson correlation coefficient, procedure of Z-transform. The sample size is 159 persons, among them: 60 persons are students of the faculty of psychology, history and sociology of Kherson State University, 63 persons are pupils of the 9–11 grades of Kherson academic lyceum named after O. V. Mishukov, 36 persons are pupils of the 9–11 grades of Kherson specialized school I–III stages № 57 and Kherson general school I–III stages № 13. The examined sample includes 65 boys and 94 girls. The results of investigation indicate the existence of three groups of positive stereotypes in perception of police: «professionalism», «exemplarity» and «consciousness» which can evidence positive changes in perception of policemen after the reform of law-enforcement authorities. The current results also confirm theoretical model used as a basis of author’s inquirer which is based on cognitive, emotional and behavioral components. Therewith the influence of level of education and gender affiliation on forming of social stereotypes in perception of image of policeman was identified.